Correction: Thermal dissociation of inter-layer excitons in MoS2/MoSe2 hetero-bilayers. Issue 22 (25th May 2017) - Mouri, Shinichiro; Zhang, Wenjin; Kozawa, Daichi; Miyauchi, Yuhei; Eda, Goki; Matsuda, Kazunari
Abstract : Correction for 'Thermal dissociation of inter-layer excitons in MoS2 /MoSe2 hetero-bilayers' by Shinichiro Mouri et al., Nanoscale, 2017, DOI: 10.1039/c7nr01598d.